2021
DOI: 10.4183/aeb.2021.83
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical System Hormones in Non-Critically ill Covid-19 Patients

Abstract: Context. The effects of COVID-19 on the adrenocortical system and its hormones are not well known.Objectives. We studied serum cortisol, serum adrenocorticotropic hormone (ACTH), and their ratio in hospitalized non-critically ill COVID-19 patients.Design. A prospective case-control study.Methods. The study participants were divided into 2 groups. Group 1 consisted of 74 COVID-19 patients. The second group consisted of 33 healthy persons. Early admission above hormones levels was determined and compared between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The study, focusing on adrenocortical system hormones, found that the baseline cortisol serum level and cortisol/ACTH ratios were significantly elevated in the patients compared to the control group. Conversely, ACTH serum levels were lower, supporting our findings (30).…”
Section: Discussionsupporting
confidence: 90%
“…The study, focusing on adrenocortical system hormones, found that the baseline cortisol serum level and cortisol/ACTH ratios were significantly elevated in the patients compared to the control group. Conversely, ACTH serum levels were lower, supporting our findings (30).…”
Section: Discussionsupporting
confidence: 90%
“…The full text of the remaining 90 articles was then reviewed for eligibility for inclusion in our meta-analyses, resulting in the exclusion of 81 articles for reasons such as being case reports, abstracts, letters, or editorials. Finally, nine studies that met our inclusion criteria were selected for analysis, and Table 1 summarizes the key characteristics of these studies [13][14][15][16][17][18][19][20][21]. Fig 1 provides a visual depiction of the number of articles included and excluded at each stage of our evaluation process, together with the reasons why certain studies were excluded.…”
Section: Study Selectionmentioning
confidence: 99%